Harmonic equivalence of the impulse loads in vibration fatigue - Ogrinec, Primož (Strojniški vestnik, 2019)
In vibration fatigue, three unique types of loads are typical: random, harmonic and impulse. In an application any of these loads are possible. A fatigue-life analysis is possible in the time and frequency domains using the frequency-response function of a structure. Recent studies demonstrated that the impulse loads influence the accuracy of a fatigue-life prediction in the frequency domain. The focus of this research is a theoretical study of an equivalent harmonic load to the impulse load on a single-degree-of-freedom system in order to investigate the feasibility of impulse loads in vibration testing. This research shows that there is a relationship between the impulse and harmonic loads that is related to the underlying dynamic properties (e.g., damping, natural frequency). Based on a theoretical analysis an experimental procedure was developed for both cases of excitation, which was able to confirm the theoretical analysis. Using the modal decomposition the single-degree-of-freedom approach can be generalized to multiple-degrees-of-freedom systems.
Keywords: fatigue life; naključne obremenitve; ne-stacionarne obremenitve; non-Gaussian loading; non-stationary loading; random loads; spectral methods; spektralne metode; stacionarne obremenitve; stationary loading; utrujanje materiala; vibracijsko utrujanje; vibration fatigue; vibration testing